2010
DOI: 10.3109/10408440903283633
|View full text |Cite
|
Sign up to set email alerts
|

Albumin and hemoglobin adducts of benzo[a]pyrene in humans—Analytical methods, exposure assessment, and recommendations for future directions

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in our environment and can cause cancer. Exposure to PAHs can be assessed by protein adduct dosimetry using benzo[a]pyrene (B[a]P) as a model compound. We present an overview of analytical methods to detect B[a]P- derived protein adducts in humans, their uses in exposure assessment, and recommendations for future research. Two major methodologies, enzyme-linked immunosorbent assay (ELISA) and chemical-specific assays, could be traced in the literature but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 87 publications
0
40
0
3
Order By: Relevance
“…One disadvantage with a tetrol of BPDE for monitoring doses in vivo is that this analyte does not provide any proof that it originates from a protein adduct. Kaefferlein et al concluded in their review that the protein adduct data from studies of humans exposed to BP are inconclusive and that there is a need for more sensitive and specific methods (Kaefferlein et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One disadvantage with a tetrol of BPDE for monitoring doses in vivo is that this analyte does not provide any proof that it originates from a protein adduct. Kaefferlein et al concluded in their review that the protein adduct data from studies of humans exposed to BP are inconclusive and that there is a need for more sensitive and specific methods (Kaefferlein et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…In vitro studies have shown that corresponding adducts to Hb and SA (from humans) are formed to specific carboxyl groups (by the formation of ester bonds) and to nitrogen atoms in specific residues (histidine (His)) (Brunmark et al, 1997;Day et al, 1994;Naylor et al, 1990). Chemical-specific methods such as GC/MS have been used to measure the BP tetrols released following the hydrolysis of the ester adducts to Hb or SA from exposed humans (reviewed by Kaefferlein et al, 2010). The ester adducts formed by BPDE with Hb in mice and rats may undergo hydrolysis in vivo, and are therefore, significantly less stable in vivo than the ester adducts formed with human Hb (Naylor et al, 1990), which are protected by the tertiary structure of the protein (Day et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…При этом не удавалось выявить АТ, специфичных к ад-дуктам БП-диолэпоксид-белок [20,32], хотя об-разование таких аддуктов с гемоглобином и аль-бумином у человека доказано [22,23,30,31,32]. Высокие уровни АТ к аддуктам БП-диолэпоксид-ДНК обнаружены у членов семей, в которых были больные РЛ и хронической обструктивной болез-нью легких [27].…”
Section: Discussionunclassified
“…Считается, что генетический полиморфизм ферментов биотрансформации низкомолеку-лярных ксенобиотиков CYP, GST является одним из эндогенных факторов канцерогенеза [1,2,21,28,30,37,38,41]. Аддукты метаболитов канце-рогенов с ДНК и белками, а также специфичные к ним АТ действительно обнаружены у людей, подвергающихся интенсивному канцерогенному воздействию [4,5,7,9,17,20,22,23,26,27,31,32,42,43]. А у больных злокачественными опухо-лями выявлено большее количество АТ к хими-ческим канцерогенам, чем у здоровых [3,12,39].…”
unclassified
“…It is highly likely that the same type of mechanism is operating in animals and fish. Naturally, adduct formation between PAH metabolites and human proteins and in particular human hemoglobin and serum albumin have been very well documented [170,[192][193][194][195][196][197][198][199]. However, there are a few studies concerning protein adducts in fish.…”
Section: Protein Adducts From Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%